TINDAK TUTUR DALAM PROSES BELAJAR-MENGAJAR PADA TAMAN KANAK-KANAK DHARMA WANITA KELURAHAN WAPUNTO KECAMATAN DURUKA KABUPATEN MUNA (KAJIAN PRAGMATIK) - Rachman; Nirmalasari (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research is entitled ‘Speech Acts in the Teaching and Learning Process at Wapunto Village Kindergarten, Duruka District, Muna Regency (Pragmatics Study)’. The background of the researcher raised the title because the ability of students in responding to the teacher's speech acts is still quite low. The problem in this research is ‘how is the form of speech acts contained in the teacher's speech in the teaching-learning process at Dharma Wanita Kindergarten, Wapunto Village, Duruka Sub-district, Muna Regency?’. The purpose of this research is to describe the forms of speech acts of kindergarten teachers in the teaching-learning process at Dharma Wanita Kindergarten, Wapunto Village, Duruka District, Muna Regency. This research is classified as field research and the method used is descriptive qualitative method. This research uses pragmatic approach. The data in this study are the speech of teachers and students of the Kindergarten. The data sources in this research are teachers and students of kindergarten. The data collection method used is the listening method using recording techniques, free-lance listening, and note taking. This research uses pragmatic analysis method in analysing the data. The data analysis technique was carried out with the stages of data transcription, data identification, data classification, data interpretation, and data description. The results obtained in this study are the speech in the teaching-learning process at Dharma Wanita Kindergarten, Wapunto Village, Duruka District, Muna Regency, there are four types of actions, namely assertive, directive, expressive and commissive actions. In this study there is no declarative action.